The right to disconnect and techno-stress in home-working: A comparative legal and psychological analysis in the European union and the Western Balkans - AGALLIU, Pjereta; IBRAHIMI, Silva (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the implications of home working, digital stress, and the right to disconnect (R2D) across six Western Balkan economies in relation to EU standards, focusing on the legal and psychosocial challenges of work digitalization. The research employs a multidisciplinary analysis of legal frameworks and workplace practices, examining employee rights, employer obligations, occupational safety and health (OSH), work hours, GDPR compliance, and social security systems in the post-COVID-19 context. Findings reveal that while all studied economies demonstrate basic remote work regulations and data protection progress, significant variations in legislative quality exist. Serbia shows notable advancement in OSH regulations, and Albania has successfully modified telework laws. However, substantial gaps persist in working hours enforcement, R2D implementation, home office OSH guidelines, and remote worker training provisions. As practical implications for organizations and policymakers, the study suggests they must prioritize developing comprehensive remote work policies, establishing clear digital boundaries, and implementing effective OSH guidelines for home offices. In conclusion, the successful integration of remote work in Western Balkan economies requires harmonization with EU standards, strengthened enforcement mechanisms, and enhanced social dialogue to ensure fair, secure, and efficient remote working conditions.